Development of E-Module Teaching Materials with a Scientific Approach: A Buddhist Learning on Educational Technology - Setiawan, Annas; Susanto, Susanto; Adi Gautama, Sidartha; Mayasari, Linda Ika (LPPM STIAB JINARAKKHITA LAMPUNG, 2024)
The purpose of this research is to develop teaching materials in the form of interactive e-modules with a scientific approach to Buddhist material and cultural diversity in Indonesia. This research and development is carried out because the learning process in schools is still conventional, namely the lecture method, and is fixated on the guidebook, and the use of media has not been carried out optimally. The delivery of each material requires a more attractive display and other supporting sources so that it is easy for students to understand. Along with technology development in the learning process, media can be used in learning materials, such as e-module teaching material products. So that students are expected to more easily understand the material and learning becomes more effective and efficient. The method used in this study is research and development or research and development (R and D) level 3. The steps used are several steps, namely researching and developing existing products. The subject of this research is students. The data collection technique uses observation sheets for product validation, the one-group pretest-posttest method, and analysis techniques using paired samples test. The overall assessment results given by the validators of material experts, media, and Buddhist teachers received an average score of 4.31 with a percentage of 86% in the very decent category.